2013
DOI: 10.1007/s10409-013-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Jet formation in shock-heavy gas bubble interaction

Abstract: The influences of the acoustic impedance and shock strength on the jet formation in shock-heavy gas bubble interaction are numerically studied in this work. The process of a shock interacting with a krypton or a SF 6 bubble is studied by the numerical method VAS2D. As a validation, the experiments of a SF 6 bubble accelerated by a planar shock were performed. The results indicate that, due to the mismatch of acoustic impedance, the way of jet formation in heavy gas bubble with different species is diversified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A common explanation is that the jet formation is a result of the shock focusing. Zhai et al 28 and Zou et al 29 discussed the effects of the shock strength and gas species on the jet formation and qualitatively concluded that it is the relative position of the shock focusing and leeward surface of the gas bubble that determines the jet formation. Georgievskiy et al 30 summarized the shock focusing locations based on numerical simulations using elliptical bubbles with different elongation ratios and density ratios, under different incident shock strengths.…”
Section: Articlementioning
confidence: 99%
“…A common explanation is that the jet formation is a result of the shock focusing. Zhai et al 28 and Zou et al 29 discussed the effects of the shock strength and gas species on the jet formation and qualitatively concluded that it is the relative position of the shock focusing and leeward surface of the gas bubble that determines the jet formation. Georgievskiy et al 30 summarized the shock focusing locations based on numerical simulations using elliptical bubbles with different elongation ratios and density ratios, under different incident shock strengths.…”
Section: Articlementioning
confidence: 99%
“…Later, these cases were numerically modelled highlighting the feature of the shock-bubble interactions [31]. Since then, many additional cases have been considered, including the bubble composition of SF6 and Krypton [33][34][35][36]. However, these studies are all conducted at atmospheric pressure and room temperature where the fluids are in a gaseous state.…”
Section: Introductionmentioning
confidence: 99%